Rule Changes to Increase Shared Medal Winning at the Olympics - Feifei Li; Will G. Hopkins (Frontiers Media S.A., 2022)
One of the most inspirational moments of the Tokyo Olympics was the sharing of the gold medal in the men's high jump. Rule changes that allow more medal sharing when athletes and teams are effectively equal in ability would improve the entertainment value of the Olympics, reward more athletes for their years of dedication to sport, and augment the Olympic ideal of fair play. Medals in all events are decided by a time, distance or points score in a final. When scores differ by ~0.1 or less of the variability in the score between competitions, the athlete or team with the better score would obtain a better score on average in only 52% of subsequent competitions, representing medals determined effectively by a coin toss. We have therefore quantified the medal sharing at the Tokyo Olympics that would have occurred if medals had been shared with such score differences (converted to rounded times or distances separating athletes in a final) in events with known variability between competitions (canoeing, kayaking, rowing, swimming, track and field events). In these events, 10%, 14% and 14% respectively of gold, silver and bronze medals would have been shared. The men's high jump would have produced three golds. Most of the sharing (68%) would have occurred with male athletes, presumably because greater depth of competition with males results in smaller differences between athletes at the highest level. The variability of performance scores in other events between competitions would need researching to establish maximum score differences for medal sharing in these events. For all events, the rule changes should exclude counting back, penalty shoot-outs, tie-breakers and any other methods for avoiding ties in the final. The acceptability of these rule changes to athletes, coaches and spectators (for example, in terms of separation of the athletes at the finishing line) would also need to be investigated.